2021
DOI: 10.2147/cmar.s319466
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis and Pathological Basis of Signal Intensity on T2-Weighted MR Images in Benign and Malignant Parotid Tumors

Abstract: To investigate the value of the signal intensity on T2-weighted magnetic resonance (MR) imaging using quantitative analysis in the differentiation of parotid tumors. Materials and Methods: MR data of 80 pleomorphic adenomas (PAs), 68 Warthin tumors (WTs), and 34 malignant tumors (MTs) confirmed by surgery and histology were retrospectively analyzed. The signal intensities of tumor, normal parotid gland, spinal cord, and buccal subcutaneous fat were measured, and the signal intensity ratios (SIRs) between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(54 reference statements)
1
0
0
Order By: Relevance
“…In both the training and validation sets, the performance of our clinical model had higher AUCs of 0.923 and 0.926 than the radiomics models, which differs from previous studies [19,21], suggesting clinical models may play a more critical role than radiomics in differentiating WT from PA. In the current study, we found that SI of WT on T2WI in the training set was significantly higher than that of PA, and SI on T1WI was the opposite, which may be related to the abundance of epithelium signals [37]. We also found that some clinical features were more common in WTs than PAs, such as a predisposition in men and smokers, which is consistent with previous reports [21].…”
Section: Discussionsupporting
confidence: 92%
“…In both the training and validation sets, the performance of our clinical model had higher AUCs of 0.923 and 0.926 than the radiomics models, which differs from previous studies [19,21], suggesting clinical models may play a more critical role than radiomics in differentiating WT from PA. In the current study, we found that SI of WT on T2WI in the training set was significantly higher than that of PA, and SI on T1WI was the opposite, which may be related to the abundance of epithelium signals [37]. We also found that some clinical features were more common in WTs than PAs, such as a predisposition in men and smokers, which is consistent with previous reports [21].…”
Section: Discussionsupporting
confidence: 92%